Point-of-care monitoring of oral anticoagulation therapy in children. Comparison of the CoaguChek XS system with venous INR and venous INR using an International Reference Thromboplastin preparation (rTF/95) - Greenway, Anthea; Ignjatovic, Vera; Summerhayes, Robyn; Newall, Fiona; Burgess, Janet; DeRosa, Lydia; Monagle, Paul (Thrombosis and haemostasis, 2009)
Point-of-care (POC) monitoring of oral anticoagulation has been widely adopted in both paediatric and adult patients. A new POC system, the CoaguChek XS has recently been developed to measure the international normalised ratio (INR) and may offer significant advantages. The CoaguChek XS utilises a new method of electrochemical clot detection based on thrombin generation. This system has not been previously evaluated in children with reference to the laboratory gold standard, the prothrombin time using reference thromboplastin. It was the objective to compare values obtained by the CoaguChek XS system with both the venous INR and the gold standard for anticoagulant monitoring, prothrombin time with reference thromboplastin (rTF/95). To evaluate the impact of testing using the CoaguChek XS on clinical anticoagulant dosing decisions. Fifty paired venous INR and capillary CoaguChek XS results were obtained from 31 children (aged up to 16 years). The laboratory gold standard, a manual prothrombin time with reference thromboplastin (rTF/95) was additionally performed on 26 samples. Correlation between the CoaguChek XS result and the venous INR was r = 0.810. Agreement between the CoaguChek XS result and the reference INR was shown to be higher (r=0.95), in the subset analysed by this method. Correlation between the venous INR and reference INR was r=0.90. Despite changes to the methodology of testing with the CoaguChek XS POC monitoring system, the accuracy of this method when compared with both the venous INR and gold standard reference INR was satisfactory. This resulted in infrequent changes to clinical decision making regarding anticoagulation.